Evolution of cyme architecture in Celastraceae - Li, Jin-Yu; Li, Yan-Nan; Tu, Qiang; Zhang, Zhi-Xiang (Phytotaxa, 2014)
Celastraceae are characterized by a cymose pattern of inflorescence ramification. Under this basic pattern, many inflorescence forms have been described within the family, e.g., dichasium, monochasium, pleiochasium, botryoid, thyrsoid, fascicle. Thus, the question has arisen—how have these varieties evolved or transformed from one to another? Through morphogenetic observations using paraffin sections, scanning electron microscopy (SEM), and stereomicroscopy, we studied the architecture and developmental processes of the inflorescences of five species of Celastrus and Euonymus. We found in C. orbiculatus that the reduction of subtending leaves of the axillary dichasia on a developing flowering shoot made it become a terminal thyrsoid. A dichasium in the leaf axil as commonly seen in Euonymus is the most frequent type of inflorescence in Celastraceae. An analysis of character evolution suggested that a dichasium is the ancestral state for Celastraceae. Therefore, within Celeastaceae, an axillary dichasium may be the basic type or unit of inflorescences. Transitions from dichasium to thrysoid and other types of cymes, and even to solitary flowers might have occurred repeatedly in the family, probably a phenomenon of evolutionary convergence due to changing environmental conditions. The present study provided helpful information for understanding the evolution of the cymose type of inflorescence in flowering plants.